Code Mixing By Jennifer Bachdim in Melaney Ricardo’s Youtube Content - Suari, Ni Kadek Maritya; Krisnawati, Ni Luh Putu Krisnawati; Rajeg, Gede Primahadi Wijaya (ENGLISH JOURNAL OF INDRAGIRI, 2026)
This research analyses the types of code mixing and the context of the situation from the code mixing used in the conversation. The study applies the theory of code mixing by Muysken and the context of the situation by Halliday and Hassan. The data sources are the selected sentences, phrases, and clauses from a video titled JEN “IRFAN LAGI TIDAK BERKERJA! JADI SEKARANG SAYA YANG KERJA!” on Melaney Ricardo's YouTube Channel that were analysed with qualitative data analysis. The result shows that three types of code mixing were found in the content. There were insertion 15 occurrences, alternation 6 occurrences, and congruent lexicalization 6 occurrences. In this case, three components of the context of situation were analysed from the conversation. There were field, tenor, and mode.